Analisis Framing Model Robert N. Entman tentang Serangan Ransomware Pada PT Bank Syariah Indonesia Tbk. - Ariyanto, Saptono (Universitas Al Azhar Indonesia, 2024)
ABSTRACT This article delves into the Framing Analysis of Ransomware Attack News at BSI across five news sources: Cyberthreat, CNN Indonesia, Kontan, Tempo, and CNBC Indonesia. The study applies social construction theory and mass media representation theory, utilizing Robert N. Entman's Framing analysis method. The research is grounded in the idea that framing encompasses issue selection and emphasis as its primary dimensions. Through a qualitative analysis approach, the investigation seeks to examine how the ransomware attack is portrayed in five distinct news articles using Entman's framing model. The findings of the study reveal distinct framing of the ransomware attack across the five media outlets. Each news article complements the others, collectively showcasing BSI's diligent efforts in managing the ransomware attack, which resulted in minimal impact deemed acceptable by shareholders. The differences in framing across the news sources highlight nuances in how the incident is depicted, shedding light on the varied perspectives and priorities emphasized by different media platforms. By employing Entman's framing model, the study underscores the importance of understanding media framing in shaping public perception and discourse surrounding cybersecurity incidents like ransomware attacks. It emphasizes the role of media in constructing narratives and influencing stakeholders' interpretations of such events, highlighting the need for a nuanced and critical approach in media analysis and consumption related to cybersecurity issues.